"I am not shy anymore": A qualitative study of the role of an interactive mHealth intervention on sexual health knowledge, attitudes, and behaviors of South African adolescents with perinatal HIV - Scarlett Bergam; Thobekile Sibaya; Nompumelelo Ndlela; Mpume Kuzwayo; Messaline Fomo; Madeleine H. Goldstein; Vincent C. Marconi; Jessica E. Haberer; Moherndran Archary; Brian C. Zanoni (BMC, 2022)
Plain Language summary South African adolescents with perinatally-acquired HIV (APHIV)-teenagers who were born with HIV-lack access to sexual and reproductive health (SRH) education specific to their HIV status. Ineffective SRH education often leads to risky behaviors (such as unprotected sex), teenage pregnancy, and the spread of HIV. Mobile health (mHealth) interventions, such as phone apps, can help improve adolescent SRH knowledge and decision-making. In this study, we evaluate how a WhatsApp-based intervention-Interactive Transition Support for Adolescents Living with HIV (InTSHA)-influences SRH attitudes and behaviors of APHIV. InTSHA involved long-term, weekly group chats of APHIV, run by trained facilitators, that included two modules discussing SRH. This study analyzes in-depth interviews we conducted with adolescents who completed InTSHA, asking them about their SRH knowledge and behaviors before and after the intervention. The interviews took place in a government-supported clinic in an urban township of KwaZulu-Natal. Interviews were recorded, transcribed, translated, coded, and analyzed. Of 21 participants, 13 were female and the average age was 16.6 years. Most participants reported first learning about SRH as young teenagers in school, through peers, or on the internet, rather than through healthcare workers or family members. Participants reported that InTSHA provided a comfortable platform to discuss relationships, gender, and sexuality as APHIV. Adolescents enjoyed giving and receiving information from peers in a moderated setting. They reported that InTSHA built their confidence, decision-making skills, and communication with partners and caregivers. South African SRH education for APHIV can be supplemented by targeted mHealth interventions.